Предмет: Алгебра,
автор: dfgcgh
допоможіть будь ласка
Приложения:
Ответы
Автор ответа:
1
1) (a² + b² -c²) - (b² +c²- a²) + (c² - a²) = a² + b² -c² - b² - c²+ a² + c² - a² =
= a² -c²
a² - c² = a² - c² доказано
2) (4 - 3a²) -a² + (7+ 2a²) - (- 2a² +11) = 4 - 3a² -a² +7+ 2a² + 2a² - 11 = 11 -11 = 0
0 = 0 доказано
3) (x³ + 4x²) - (x + 6) + (1 + x - x³) = x³ + 4x² - x - 6 + 1 + x - x³ = 4x² -5
4x² - 5 = 4x² - 5 доказано
Похожие вопросы
Предмет: Биология,
автор: cuzelalimova20
Предмет: Математика,
автор: aiwa12345
Предмет: Геометрия,
автор: pikaposty
Предмет: Биология,
автор: AndrewWDolD
https://znanija.com/task/39957849?utm_source=android&utm_medium=share&utm_campaign=question